Is annual surveillance of all treated hypothyroid patients necessary? - Pereira Olivia; Dalziel Katherine; MacLennan Graeme; Acharya Shamsunder H; Philip Sam; Avenell Alison; Viswanath Ananth K; Copland Shirley A; Bevan John S; Abraham Prakash (BMC Endocrine Disorders, 2007)
Abstract Background Annual surveillance (with thyroid function testing) is widely recommended for the long-term follow-up of treated hypothyroid patients. It is based largely on consensus opinion and there is limited evidence to support the frequency of monitoring. The majority of patients in our hospital based thyroid register are on 18 monthly follow-up. Methods We carried out a retrospective analysis to see if there is evidence to support more frequent testing. We used a logistic regression model to assess whether any baseline characteristics could be applied to predict an abnormal test. Results We identified 2,125 patients with a minimum of 10 years follow-up (89% female, 65% autoimmune hypothyroidism, and mean age at registration 51 years). There were 2 groups: 1182 (56%) had been allocated to 18 monthly follow-up and the rest had annual surveillance. The groups were well matched at baseline. Overall, during follow-up the 12 monthly group had more abnormal tests requiring dose adjustment. However, on logistic regression analysis, people aged less than 60 years, individuals taking < 150 μg thyroxine per day and people on 18 monthly follow-up had less abnormal tests. Conclusion 18 monthly surveillance may be adequate in the long term follow-up of hypothyroid patients less than 60 years of age on a stable thyroxine dose of 100–150 μg/day where there are robust follow-up mechanisms in place. Implementing this strategy has potential for cost saving.